2020
DOI: 10.4269/ajtmh.20-1553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 Infection in Pregnancy on Maternal and Neonatal Outcomes in Africa: An AFREhealth Call for Evidence through Multicountry Research Collaboration

Abstract: . In the African context, there is a paucity of data on SARS-CoV-2 infection and associated COVID-19 in pregnancy. Given the endemicity of infections such as malaria, HIV, and tuberculosis (TB) in sub-Saharan Africa (SSA), it is important to evaluate coinfections with SARS-CoV-2 and their impact on maternal/infant outcomes. Robust research is critically needed to evaluate the effects of the added burden of COVID-19 in pregnancy, to help develop evidence-based policies toward improving maternal and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…Unfortunately, the spread of the disease elsewhere in Africa has been less well characterised, with only a few small observational studies documenting the effect of COVID-19 on African pregnant women. [28] Etti et al [5] plan to address some of these knowledge gaps by screening >50 000 pregnant women from five sub-Saharan countries, which will provide more information on the burden of COVID-19 in pregnant women on the continent.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Unfortunately, the spread of the disease elsewhere in Africa has been less well characterised, with only a few small observational studies documenting the effect of COVID-19 on African pregnant women. [28] Etti et al [5] plan to address some of these knowledge gaps by screening >50 000 pregnant women from five sub-Saharan countries, which will provide more information on the burden of COVID-19 in pregnant women on the continent.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…HIV-infection and/or tuberculosis independently predicted the hazard of death in South Africa [ 12 ] and of severity in Ethiopia [ 27 ], but not in studies from the USA [ 15 , 28 ]. As such, the call by The African Forum for Research and Education in Health [ 6 , 7 ] to pool COVID-19 data from African countries very necessary to enhance COVID-19 epidemiology in Africa to ensure an adaptive response at both hospital and community levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature on COVID-19 is growing at an exponential pace, there is still a shortage of observational studies from several African countries. However, local epidemiology is essential to enable the adaptation of the evidence-based response of COVID-19 at local levels as well as national and regional levels, once pooled [ 6 , 7 ]. For example, in typical resource constrained settings, not every facility would have adequate intensive care beds, access to ventilators, continuous oxygen, CT scanners, or even basic biological testing kits.…”
Section: Introductionmentioning
confidence: 99%
“…As is now apparent, many aspects of research and teaching can be continued quite effectively via virtual platforms like Zoom and others. A successful example of the leverage of virtual video platforms for research collaborations is demonstrated by AFREhealth's multi-country, South-South COVID-19 research project among pregnant women and children [7,8]. While deficiencies and concerns in education (especially clinical teaching and training) remain, several have been quite effectively addressed in some form through video-enhanced platforms like Lecturio, Osmosis, and Scholar-X [6].…”
Section: Rethinking Global Health Partnerships: Research and Educationmentioning
confidence: 99%
“…Such initiatives will also strengthen Southto-South multi-disciplinary and interprofessional research collaborations. AFREhealth's COVID-19 Research Working Group has embarked upon such a collaboration across Western, Central, Eastern, and Southern Africa [7,8].…”
Section: South-south and North-south Research Collaboration And Capacity Buildingmentioning
confidence: 99%